2009
DOI: 10.1292/jvms.001357
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Epidemiological and Serological Studies of Hantavirus Infection in Northern Vietnam

Abstract: ABSTRACT. The distribution of anti-hantavirus antibodies in humans and rodents in northern Vietnam was examined. In total, 837 serum samples from healthy humans (617) and patients with fever (220), living in six different areas were screened for IgG antibodies against Hantaan or Seoul virus (SEOV) by ELISA, IFA, and Western blot analysis. Antibody-positive sera were identified in 7/617 (1.1%) healthy donors, 5/150 port workers in the port of Hai Phong, and 2/185 residents of Ha Nam Province. In comparison, pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
27
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 29 publications
7
27
0
Order By: Relevance
“…Among those viruses, THAIV can cause disease in humans (Pattamadilok et al, 2006;Gamage et al, 2011). Epizootiology studies have reported the presence of rats in Vietnam and Singapore with antibodies against SEOV (Truong et al, 2009;Johansson et al, 2010). SEOV has also been detected in rodents from Indonesia (Ibrahim et al, 1996).…”
Section: Pathogenic Hantaviruses and Their Reservoirsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among those viruses, THAIV can cause disease in humans (Pattamadilok et al, 2006;Gamage et al, 2011). Epizootiology studies have reported the presence of rats in Vietnam and Singapore with antibodies against SEOV (Truong et al, 2009;Johansson et al, 2010). SEOV has also been detected in rodents from Indonesia (Ibrahim et al, 1996).…”
Section: Pathogenic Hantaviruses and Their Reservoirsmentioning
confidence: 99%
“…SEOV infection, like dengue fever, has also been reported in Malaysia (Hamidon and Saadiah, 2003). Serological evidence of hantavirus infections in humans, particularly in patients with fever of unknown origin, has been reported in Vietnam, Singapore, Laos, Thailand, Malaysia, and Indonesia (Rollin et al, 1986;Lam et al, 2001;Groen et al, 2002;Truong et al, 2009). In Thailand, cases of coinfection with hantavirus and leptospirosis have been detected (Gamage et al, 2011).…”
Section: Asian-pacific Countriesmentioning
confidence: 99%
“…Seroprevalence described in this study can not be directly compared to the published results of serological studies on reservoir rodents [1,9,16], because detection accuracy may be different. However, this is the first report of the existence of hantavirus in the eastern Africa.…”
mentioning
confidence: 97%
“…In other East Asian countries, such as Thailand, Indonesia, Vietnam, Sri Lanka and India, prevalence of SEOV and THAIV infection has been shown among rodents and humans [2,3,6,13,14,16,17,22].…”
mentioning
confidence: 99%
“…Furthermore, we have reported a HFRS case of SEOV infection in Ho Chi Min City (HCMC) [2]. Interestingly, seropositive persons in rural areas were suspected to have been infected with a hantavirus that was antigenically different from previously reported hantaviruses such as SEOV, HTNV and THAIV [22]. That report indicated that a variety of novel hantaviruses might exist in Vietnam.…”
mentioning
confidence: 99%